Diffraction-based misorientation mapping: A continuum mechanics description. (December 2019) - Rui, Shao-Shi; Niu, Li-Sha; Shi, Hui-Ji; Wei, Shaolou; Tasan, C. Cem
Highlights: KAM results from three GND density tensor in-surface invariants and three elastic strain modes. GROD corresponds to neither local plastic strain nor local material rotation alone in SC samples. "V-type"GROD distribution near the neutral surface of a SC sample reflects its buckling curvature. Averaged KAM ¯ and GROD ¯ are proven to correlate with nominal plastic strain linearly in PC samples. Abstract: As the typical intragranular misorientation parameters, Kernel Averaged Misorientation (KAM ) and Grain Reference Orientation Deviation (GROD ) are widely used in diffraction-based misorientation mapping, while their evolution laws under various conditions and physical meanings in continuum mechanics description are rarely investigated systematically. Therefore, we designed several comparative experiments considering the influences of grain boundaries (single-crystalline vs. poly-crystalline), sample geometries (smooth vs. notched) and plastic strain modes (tension vs. buckling) onKAM &GROD evolution, and captured the intragranular misorientation, dislocation density, and material distortion synchronously based on coupled EBSD-ECCI-DIC mapping in this research. Meanwhile, we also discussed the physical meanings ofKAM &GROD based on continuum mechanics description and provided the theoretical explanations to phenomena observed in the above experiments.KAM results from three in-surface invariants ( ρ GND I, ρ GND II & ρ GND III ) of GND density tensor ρ GND induced by plastic strain distribution incompatible with the activated slip systems in unloaded elastic-plastic condition, which cause the same lattice curvature effects as three elastic strain modes with non-zero curl (buckling, in-surface bending & torsion) in purely elastic condition.GROD reflects neither local plastic strain nor local material rotation alone, but its "V-type" distribution near the neutral surface reflects the buckling curvature of single-crystal. Besides, KAM ¯ & GROD ¯ averaged over multiple grains can be used to estimate the nominal plastic strain applied in poly-crystal. Graphical abstract: Image, graphical abstract